تكوين البيئة اللغوية لترقية مهارة الكلام في دورة مركز العربية بباري كديري - نور المقدمة, حبي; مزيدة, نور (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
The linguistic environment is useful and influential in developing Arabian Center students' speaking skills. This research aims to explore the process of forming an active Arabic language environment through several efforts that must be implemented in forming this environment. This research also aims to find out what problems are faced in creating an active Arabic language environment, as well as the solutions. This study used descriptive qualitative method. The techniques used to collect data are observation, interviews and documentation. To carry out data analysis, analytical theory according to Miles and Huberman was used. In the data validation stage, the two researchers used the triangulation method. Research results: Efforts to form a linguistic environment, including: the role of the head of the linguistic department, the linguistic system, the linguistic court, the formation of an executive department in the linguistic environment, and many other programs. In carrying out these efforts of course there will be problems, including: lack of officer control and cooperation in crimes, as well as a sense of seniority that arises within the residence. Therefore, this problem can be resolved by appointing a substitute professor to review the report once a week and provide a warning message